Differences between parameters of situational efficiency according to level of competition in Croatian handball leagues (case study) - Belcic, I.; Sporic, G. (Acta Kinesiologica, 2012)
The purpose of this study was to determine differences between the parameters of situational efficiency in selected games according to the level of competition in the Croatian handball leagues. The sample consisted of 4 handball matches with 8 teams in selected league matches who play 3rd Croatian national handball league north, 2nd Croatian national handball league north, 1stB Croatian national handball league and Premier Croatian national handball league. Analysis of the players was conducted in four matches, and analysed by one game in each level of competition. With t - test for independent samples, there are statistically significant differences in variables blocked balls, dribbling faults and turnovers. Statistically significant differences have been established between Croatian handball leagues in this specific sample.